A 46.5-dB Range, High Linearity, Low Power, Baseband Programmable Variable Gain Amplifier - Yaser A. Khalaf, Mohamed F. Ibrahim, Ibrahim L. Abdalla (International Journal of Advanced Science and Technology, 2020)
A new design of a fully-differential programable variable gain amplifier (PVGA) is proposed. The PVGA consists of just two stages, a transconductor followed by a transresistor, using only two high-gain opamps and inverters. The high-gain opamps afford good linearity and small gain-step error.Moreover, most critical signal nodes are low impedance current-mode points; leading to a wide bandwidth. The PVGA is designed and simulated in a 0.13 mm CMOS process. The power consumption is 574 mW from a supply voltage of 1.2V. The simulation results show accurate linear-in-dB gain variation with a large gain dynamic range between 0 dB and 46.5 dB with a gain step of 1.5 dB. The PVGA exhibits high linearity;the output 1-dB compression point is higher than 10.5 dBm.